Efeito da aspersão de água sobre a contaminação microbiológica em esteiras transportadoras de cortes de frango - Soares, Vanessa Mendonça [UNESP] (2014)
This study aimed to evaluate the effect of the use of water spray on cleaning of conveyor belts in four broiler lines processing in Brazilian slaughterhouses. Surface samples were collected of two types of conveyor belt (modular and smooth) which passed through two processes (with and without water spray), in four times (T0, T1, T2 and T3). The samples were subjected to mesophilic and enterobacteria count, and research of L. monocytogenes. Cultures of L. monocytogenes were serotyped and submitted to PFGE. Ten replicates of the experiment were performed on each processing line. The results demonstrated that the effect of the use of spraying with water was dependent on several factors, such as the processing line, product type, equipment design and the type of conveyor belt. The cleaning spray is not the primary factor in ensuring the elimination of L. monocytogenes, because the pathogen was isolated independent of the type of conveyor belt and processing line, moreover, PFGE demonstrated the dissemination in the processing lines. Thus, the decision to remove the water from the cleaning of conveyor belts must be preceded by a study to ensure that the absence of this procedure does not influence the safety of products of animal origin